Business Development of Digital Tenun Nusantara (Ditenun) Using Business Model Canvas and SWOT Analysis - Monica Butarbutar; Hansel Septiyan Pasaribu; Noramti Mardianti Manurung; Ricton Samuel Sitorus; Arlinta Christy Barus; Febriani Gultom; Humasak Tommy Argo Simanjuntak; Nancy Panjaitan; Wesly Mailander Siagian (School of Business, IPB University (SB-IPB), 2023)
DiTenun is a start-up engaged in traditional woven fabrics. The main product of DiTenun is the technology that can create woven motifs using artificial intelligence. In running the business, DiTenun is still experiencing stagnation in its development so that DiTenun continues to make efforts to develop its business. One of these efforts is to participate in the Kedaireka Matching Fund program offered by the Ministry of Education and Culture. This program requires DiTenun to cooperate with Batikta and Kaldera. To support this collaboration, it is necessary to know Dtenun business model's description to make the collaboration flow more focused. Therefore, this research aimed to discover the description of the DiTenun business model and its business collaboration. Canvas Business Model was used to determine the business strategy and was tested using SWOT planning method to evaluate the project's strengths, weaknesses, opportunities and threats or business speculation. From the BMC (Canvas Business Model) that has been designed for weaving, the company are recommended to further develop it in the elements of several elements. On the key activities element, it can focus on building a community of weavers when marketing expansion is better at selling its products. On the key partner element, it can expand its partners to the ones who can make DiTenun more developed, both in terms of business and production. On key resource elements, they can further develop their technology so that they can produce more perfect motifs and can be much easier for weavers to understand. Another essential thing that DiTenun needs to pay attention to is participating in critical programs to help DiTenun expand its business. Keywords: ditenun, start-up, business model canvas, swot, business development